Romantic gothic : an Edinburgh companion - Wright, Angela, 1969 May 14-; Townshend, Dale; Saglia, Diego (Edinburgh companions to the gothic., 2016)
Romantic Gothic: An Edinburgh Companion provides a thorough critical, textual and historical account of the Gothic aesthetic as manifested across a wide range of Romantic-era literary texts, from the adumbrations of the Gothic mode in the proto-Romantic poetry of the 1740s, through to the"belated" Gothic fictions of the late 1820s. Self-consciously breaching, like Hume and Gamer before it, the critical divide between what literary history has subsequently differentiated as the "Gothic" and the "Romantic", this collection of 17 newly commissioned chapters seeks to draw attention towhat G.R. Thompson in 1947 termed "dark Romanticism", that is, that prominent strain in late eighteenth and early nineteenth-century British, American and European literature in which the distinction between the popular, low-cultural reaches of the Gothic and the 'High' Romantic aesthetics of morecanonical figures is all but erased. The Edinburgh Companions to the Gothic series provides a comprehensive overview of the Gothic from the eighteenth century to the present day. Each volume in this series takes either a period or a theme and explores their diverse attributes, contexts and texts via completely original essays. Eachvolume provides an authoritative critical tool for both scholars and students of the Gothic